Life Cycle Assessment (LCA) Emisi Gas dan Partikulat pada Proses Produksi Pelumas di PT. XYZ - Nina Kurnia Ningrum; Dika Rahayu Widiana; Ahmad Erlan Afiuddin (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2020)
PT XYZ produces 29500 tons/year of lubricants using used oil as raw material. The use of raw materials and resources produces air emissions that have a negative impact on the environment, therefore need an action to reduce these impacts. The purpose of this research is to recommend air emission mitigation in accordance with the highest environmental impact generated by the lubricant production process based on the Life Cycle Assessment (LCA) method using SimaPro 9.0 software. The scope of the system in this research is the gate to gate in the regenerative base oil production process (refinery) which consists of preflash, Thermal De Asphalting (TDA), Hydrofinishing (HDF) units and Lube Oil Blending Plant (LOBP) process which consists of mixing and filling units. The research steps refer to ISO 14040 in 2006 which consists of: (1) goal and scope definition, (2) Life Cycle Inventory (LCI), (3) Life Cycle Impact Assessment (LCIA), and (4) interpretation. The results showed that the lubricant production process had a major impact on global warming of 100a with a value of 230,743 Pt. The processing unit that has the greatest contribution to the impact of global warming 100a is Thermal De Asphalting with a value of 115,938 Pt. The proposed emission mitigation is Waste Heat Recovery Power Generation (WHRPG), Carbon Capture Storage (CCS), and the use of oil sludge as fuel.